METHODOLOGY FOR CHECKING THE SPEECH OF PRESCHOOL CHILDREN WITH MENTAL RETARDATION (American Journal of Pedagogical and Educational Research, 2023)
In the article, the connection of the vocabulary of mentally retarded children with mental development, speech disorders that appear in retarded mental development, and specific aspects of cognitive processes of mentally retarded children. identification, research and educational processes of effective ways of using corrective and developmental technologies in the development of the vocabulary of mentally retarded children, the level of development of mental functions important in the process of working on the vocabulary of mentally retarded children of preschool age and on the vocabulary the efficiency of the work process is highlighted.